Do wild Red-legged Partridges (Alectoris rufa) use feeders? An investigation of their feeding patterns using camera trapping. (1st February 2015) - Armenteros, J.A.; Sánchez-García, C.; Prieto, R.; Lomillos, J.M.; Pérez, J.A.; Alonso, M.E.; Gaudioso, V.R.
This paper explores feeding patterns of wild Red-legged Partridges (Alectoris rufa) at artificial feeders, a common management action for game species. Feeders were studied during two consecutive periods from October 2009 to May 2011 in an agricultural area of northwest Spain. Camera trapping was used in order to assess climatic effects on weekly feeding patterns, investigate the influence of shrub cover on feed-site selection and evaluate behavioural patterns displayed when using feeders. Red-legged partridges used feeders throughout the study period, but particularly from December to February. No significant correlations were observed between the weekly number of photographs and climate conditions. A bimodal circadian feeding pattern was observed during daylight hours with peaks of activity in the morning and evening while, in central hours, the feeding visits decreased. We observed significant differences in the number of partridges photographed during the feeding visits along the study period. The use of feeders was not influenced by the presence of surrounding vegetation nor type of feeder. The behavioural analysis classified partridges in five different categories: feeding (33.5 and 32.3% for each period respectively), vigilance (26.8 and 30.7%), moving/unknown (25.9 and 20.6%), pecking/ dusting (11.2 and 15%) and other behaviours (2.8 and 1.8%). The percentage of vigilant birds photographed at feeders was not related to the covey size. This study demonstrates the use of the feeders by Red-legged Partridges but does not prove the potential benefits.